Analisa Ornamen Bangunan Pendopo Agung Majapahit (Mojokerto Jawa Timur) dan Mataram (Pura Mangkunegaran Solo Jawa Tengah) - Setiawan, Trianita Anugerah; Abioso, Wanita Subadra (ARTic, 2022)
This study raises the comparison of the building of the Great Hall of Majapahit (Mojokerto, East Java) and the Great Hall of Mataram Pura Mangkunegaran (Solo, Central Java). philosophy in a different way. Both are historical buildings that are directly related to the history of the Mataram Kingdom and the Majapahit Kingdom, which in general, the two kingdoms still have ties to one another due to the journey of the Hindu-Buddhist religion. Inside the interior of the Pendopo Agung there are several ancient ornaments which have an aesthetic function and symbolic meaning. This study aims to analyze the comparison of forms and aesthetic and symbolic functions of the ornaments of the Great Hall. The method used is descriptive method. Data collection was obtained from observation and literature. The emergence of the Pendopo Agung building is a work created from generation to generation, guided by predetermined standard rules both technically and religiously which are interrelated to the Javanese standard. The conclusion of this study is to add insight that in each ornament on the same building has a way of conveying different meanings to the people, these differences can later be used as points of interest for each building of the Great Majapahit and Mataram Halls.